Powering progress: Clean energy and industrialization as pathways to sustainable development in Asia - Shailender Singh; Meenakshi Kaul; Chandrashekhar J. Rawandale; Muhammad Muazu Bala (Energy Policy, 2026)

Sunlight-activated BiOCl@ZnO core-shell-like heterostructures for the efficient removal of dye pollutants - Mukesh K. Verma; Muhammad D. Bala; Phindile B. Khoza; Tshephiso R. Papo; Mzamo L. Shozi (Next Research, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

The carcinogenic risks of military explosives: mechanisms, health impacts, and environmental consequences of chemical munitions - Madinat Hassan; Taofeek Tope Adegboyega; Sunday Zeal Bala; Jemila Saleh; Muhibat Bolanle Komolafe; Maryam Yahaya Muhammad; Daniel Danladi Gaiya; Amina Shehu Bature; Miracle Uwa Livinus (Toxicology and Environmental Health Sciences, 2025)

Near-surface seismic refraction anomalies due to underground target models and the application in civil and environmental engineering - Joseph Omeiza Alao; Kolawole Muideen Lawal; Bala Bello Muhammad Dewu; Jimoh Raimi (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Improving Short-term Daily Streamflow Forecasting Using an Autoencoder Based CNN-LSTM Model - Umar Muhammad Mustapha Kumshe; Zakariya Muhammad Abdulhamid; Baba Ahmad Mala; Tasiu Muazu; Abdullahi Uwaisu Muhammad; Ousmane Sangary; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Mosaad Ali Hussein Ali; Aliyu Uthman Bello; Muhammad Muhammad Bala (Water Resources Management, 2024)

Correction to: Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Construction of multi-purpose geophysical test site on a lateritic clay soil - Joseph Omeiza Alao; Kolawole Muideen Lawal; Bala Bello Muhammad Dewu; Jimoh Raimi (Arabian Journal of Geosciences, 2024)

Exploring the mechanisms and impacts of melatonin on fish colouration - Muhammad Mubashshir; Nabeel Ahmad; Tripti Negi; Renu Bala Sharma; Helen Nilsson Sköld; Mohd Ovais (Fish Physiology and Biochemistry, 2023)

The evolving roles of geophysical test sites in engineering, science and technology - Joseph Omeiza Alao; Kola Muyideen Lawal; Bala Bello Muhammad Dewu; Jimoh Raimi (Acta Geophysica, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Cryogenian crustal evolution in western Nigeria shield: whole-rock geochemistry, Sr-Nd and zircon U-Pb-Hf isotopic evidence from Bakoshi-Gadanya granites - Safiyanu Muhammad Elatikpo; Huan Li; Han Zheng; Musa Bala Girei; Jinghua Wu; Abdulgafar Kayode Amuda (International Geology Review, 2022)

Sub-acute toxicity study on hydromethanolic leaves extract of Combretum hypopilinum (Combretaceae) Diels in Wistar rats - Mubarak Hussaini Ahmad; Abdulkadir Umar Zezi; Sherifat Bola Anafi; Omar Yahya Alshargi; Mustapha Mohammed; Sagir Mustapha; Auwal Adam Bala; Surajuddeen Muhammad; Sa’adatu Muhammad Julde; Abubakar Sadiq Wada; Abubakar Ibrahim Jatau (Toxicological Research, 2022)

Health risk associated with heavy metal contamination of vegetables grown in agricultural soil of Siran valley, Mansehra, Pakistan—a case study - Muhammad Asif Tahir; Hamayun Shaheen; Bala Rathinasabapathi (Environmental Monitoring and Assessment, 2022)

Genesis and timing of Mo mineralization in the Mada Ring Complex, north-central Nigeria: insights from whole-rock geochemistry, Nd-Sr isotopes, zircon U-Pb-Hf isotopes, and molybdenite Re-Os systematics - Musa Bala Girei; Huan Li; Victor Ikechukwu Vincent; Thomas J. Algeo; Safiyanu Muhammad Elatikpo; Saleh Ibrahim Bute; Hafizullah Abba Ahmed; Abdulgafar Kayode Amuda (Mineralium Deposita, 2022)

Petrogenesis of the peralkaline Dutsen Wai and Ropp complexes in the Nigerian younger granites: implications for crucial metal enrichments - Abdulgafar Kayode Amuda; Xiaoyong Yang; Jianghong Deng; Mohamed Faisal; Jinya Cao; Saleh Ibrahim Bute; Musa Bala Girei; Safiyanu Muhammad Elatikpo (International Geology Review, 2021)

Irrigation management in Nigeria: Lessons from the Kano River irrigation scheme* - Esther Oyeronke Oluniyi; Muhammad Sani Bala (Irrigation and Drainage, 2021)
Nigeria has, in the past, tried various rural development strategies to achieve agricultural development and national food security. Among these has been the setting up of farm settlement schemes, marketing boards, the Agricultural Credit Guarantee Scheme, Operation Feed the Nation, the Land Use Decree, etc. These could not achieve much because of various political, economic and social characteristics of the Nigerian population. As a further step, river basin development authorities (RBDAs) were established. The objectives of the RBDAs and their geographical coverage brought the confidence and the possibility of finally achieving the goal of rural transformation. However, like other schemes, the RBDAs are beset with problems which are also inherent in the present economic set‐up of the country, and which would require double the energy spent in the past, to have the RBDAs perform the wonders , which the other strategies have failed to achieve. In redoubling efforts towards improved rural transformation, participatory irrigation management (PIM) began to occupy the irrigation space of the RBDAs, especially in the northern part of the country in the mid‐1990s. These efforts were then met with challenges that threatened the PIM initiatives a few years after inception. This paper examines these challenges and the current efforts by government in addressing the challenges, with a view to refocusing future public irrigation development and management in Nigeria.

Linear regression models for estimating true subsurface resistivity from apparent resistivity data - Sabiu Bala Muhammad; Rosli Saad (Journal of Earth System Science, 2018)

Rapid injuries of high temperature in plants - Gurpreet Kaur Goraya; Balraj Kaur; Bavita Asthir; Shashi Bala; Gurpreet Kaur; Muhammad Farooq (Journal of Plant Biology, 2017)

Isolation and phylogenetic analysis of caprine Orf virus in Malaysia - Ashwaq Ahmed Abdullah; Muhammad Farid Bin Ismail; Krishnan Nair Balakrishnan; Jamilu Abubakar Bala; Homayoun Hani; Yusuf Abba; Mohd Kamaruddin Awang Isa; Faez Firdaus Jesse Abdullah; Siti Suri Arshad; Zeenatul Allaudin Nazariah; Rasedee Abdullah; Noordin Mohamed Mustapha; et al. (VirusDisease, 2015)

Developmental toxicity of pyrethroids - Bala Muhammad; Richard Verschoyle; David Ray (Archives of Toxicology, 2003)